2015
DOI: 10.5194/bg-12-1387-2015
|View full text |Cite
|
Sign up to set email alerts
|

Rapid acidification of mode and intermediate waters in the southwestern Atlantic Ocean

Abstract: Abstract.Observations along the southwestern Atlantic WOCE A17 line made during the Dutch GEOTRACES-NL programme (2010)(2011) were compared with historical data from 1994 to quantify the changes in the anthropogenic component of the total pool of dissolved inorganic carbon ( C ant ). Application of the extended multilinear regression (eMLR) method shows that the C ant from 1994 to 2011 has largely remained confined to the upper 1000 dbar. The greatest changes occur in the upper 200 dbar in the Subantarctic Zon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 59 publications
4
29
0
Order By: Relevance
“…Data on the distributions of the macronutrient elements N, P, Si [44,[62][63][64][65][66][67], the micronutrient elements Fe, Mn, Ni, Zn and Cd [64,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] and the non-nutrient element Al [67,85,86] were downloaded from the IDP2014 collection [20] and imported into a Matlab™ environment for analysis. For each sampling location and/or seawater volume/water mass, a ranking of the relative deficiencies of multiple nutrient elements was calculated by dividing observed dissolved concentrations by an assumed 'typical' stoichiometric ratio within newly formed organic (biological) material (figure 1) [11,18].…”
Section: Methodsmentioning
confidence: 99%
“…Data on the distributions of the macronutrient elements N, P, Si [44,[62][63][64][65][66][67], the micronutrient elements Fe, Mn, Ni, Zn and Cd [64,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] and the non-nutrient element Al [67,85,86] were downloaded from the IDP2014 collection [20] and imported into a Matlab™ environment for analysis. For each sampling location and/or seawater volume/water mass, a ranking of the relative deficiencies of multiple nutrient elements was calculated by dividing observed dissolved concentrations by an assumed 'typical' stoichiometric ratio within newly formed organic (biological) material (figure 1) [11,18].…”
Section: Methodsmentioning
confidence: 99%
“…Salt et al (2015) reported rapid acidification of the AAIW in the southwest Atlantic. More to the south in the Weddell Gyre, nutrient concentrations significantly increased in the surface and bottom layers from 1996 to 2011 .…”
Section: Essowè Panassa Essowepanassa@awidementioning
confidence: 99%
“…In addition to changes in upwelling frequency and intensity (Jarre et al, 2015;Lamont, García-Reyes, et al, 2018;Tim et al, 2015), shifts in the properties of upwelling source waters have also been noted in the South Atlantic (de Souza et al, 2018;Karstensen & Quadfasel, 2002;Salt et al, 2015;Venegas et al, 1998). While the impacts of such changes have not been described for the BUS, increased biomass and production in the California upwelling system have been related to elevated nitrate levels in source waters (Bograd et al, 2015;Rykaczewski and Dunne, 2010).…”
Section: 1029/2018jc014334mentioning
confidence: 99%